PENGARUH REWARD TERHADAP DISIPLIN KERJA KARYAWAN PT. CITRA RIAU SARANA KABUPATEN KUANTAN SINGINGI - Dita Asriani Asriani; Gimin '; Syakdanur Nas Nas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study was motivated by the importance of the reward system in improving employee discipline PT. Citra Riau Sarana which is a company engaged in plantation and palm oil processing .. The population in this study were all employees of PT. Citra Riau Sarana totaling 109 people. The sample in this study is the number of employees of PT. Citra Riau Sarana numbering 109 people with 10% precision level set. The data used in this study are primary data and secondary data. Analysis of the data used is using simple linear regression analysis with significance level of 5%. Data processing is done with the help of SPSS software version 17.0. From the results of simple linear regression analysis reward (X) to the discipline of employees (Y) obtained a regression equation one predictor is Y = 76.068 + 1,265X. the coefficient of determination (R2) of 0.256. This means that the influence of reward contribution to the discipline of employees of PT. Citra Riau Sarana 25.6% rise and fall of the value of labor discipline employees affected by reward, while 74.4% is influenced by other variables not examined in this study. Keywords : Reward , Labor Discipline